Analisa Penerapan Total Productive Maintenance Menggunakan Metode Overall Equipment Effectiveness pada Mesin Press Sinohara 55 T di PT. Ciptaunggul Karya Abadi - Sekar Mustika Ayuningtyas; Dene Herwanto; Samitha Pujia Khan; Zaskya Indah Vindari; Adinda Gita Azzahra; Wagiana Rohmah (Fakultas Teknik, 2023)
Many things must be considered in a production system in the industrial world, such as the performance of a machine or tool used. Productivity is closely related to smooth production. The low productivity of the machine will cause losses for the company, where this loss is caused by the use of ineffective and inefficientmachines. This study aims to determine the performance of the machine and the factors that cause damage to the press machine at PT Ciptaunggul Karya Abadi. The research was conducted using the application of TPM (Total Productive Maintenance) to increase productivity and maximize facilities. TPM is also accompanied by the OEE (Overall Equipment Effectiveness) method to measure the performance and accuracy of the machine used. This data is in the form of quantitative which is calculated using the methods mentioned above. The results showed that the average value of the availability rate was 95%, the performance rate was 87% and the quality rate was 99%. From these results, it can be seen that only the performance rate does not meet world-class standards. This is also obtained from the calculation of the six big losses, the largest percentage is in idle and minor stoppage losses, which is 47%. Alternative repair solutions can be carried out by implementing machine maintenance and continuous improvement,providing special training for operators, and reducing non-productive time.